2015
DOI: 10.1007/s11746-015-2704-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heat‐Induced Degradation of Virgin Olive Oil Using Front Face Fluorescence Spectroscopy and Chemometric Analysis

Abstract: A simple setup using a 365‐nm light‐emitting diode coupled to a USB spectrometer through an optical fiber, in a front‐face fluorescence configuration, was used to investigate the heat‐induced deterioration of virgin olive oil at different heating temperatures and times. The samples were heated for 30, 60, 120 and 180 min for every temperature setting of 140, 160 and 180 °C, respectively. Two important results are reported in this article. First, a neo‐formed compound around 665 nm due to the degradation of chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In comparison, ROO obtained from VOO has undergone multiple refining steps to ensure the product that has a low free acidity expressed as the oleic acid value (less than 0.3 g per 100 g), which is induced by the hydrolysis of triglycerides. , Due to these refining steps, ROO contains very little chlorophyll, and the EEM fluorescence fingerprint of ROO exhibits only one emission band from 350 to 520 nm (Figure b). This band is attributed to primary oxidation products (e.g., conjugated peroxides) and secondary oxidation products (e.g., aldehydes and ketones). , Additionally, the BOO in our experiment was produced by mixing EVOO with ROO, and the corresponding fluorescence fingerprint contained both spectral features of EVOO and ROOtwo emission bands ranging from 650 to 690 nm (similar to EVOO) and from 350 to 520 nm (similar to ROO), respectively (Figure c). These experiments demonstrated the rapid acquisition and ease of qualitative analysis of EEM fingerprinting to distinguish various olive oils.…”
Section: Resultsmentioning
confidence: 66%
“…In comparison, ROO obtained from VOO has undergone multiple refining steps to ensure the product that has a low free acidity expressed as the oleic acid value (less than 0.3 g per 100 g), which is induced by the hydrolysis of triglycerides. , Due to these refining steps, ROO contains very little chlorophyll, and the EEM fluorescence fingerprint of ROO exhibits only one emission band from 350 to 520 nm (Figure b). This band is attributed to primary oxidation products (e.g., conjugated peroxides) and secondary oxidation products (e.g., aldehydes and ketones). , Additionally, the BOO in our experiment was produced by mixing EVOO with ROO, and the corresponding fluorescence fingerprint contained both spectral features of EVOO and ROOtwo emission bands ranging from 650 to 690 nm (similar to EVOO) and from 350 to 520 nm (similar to ROO), respectively (Figure c). These experiments demonstrated the rapid acquisition and ease of qualitative analysis of EEM fingerprinting to distinguish various olive oils.…”
Section: Resultsmentioning
confidence: 66%
“…We used the experimental setup described by Mbesse et al [15]. A light emitting diode (LED) with an emission wavelength at 365 nm, is used as the excitation source.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…Several studies have reported successful applications of oil autofluorescence in the analysis of oil oxidation [18][19][20][21][22][23][24][25][26][27]. Various measurement techniques were used in these studies, including measurements of excitation spectra [18], emission spectra [22,25,26], synchronous fluorescence spectra [19][20][21], and excitation-emission matrices [23,24,27]. This last technique provides the most comprehensive characteristics of fluorescent systems, because excitation-emission matrices are determined by both absorption and emission properties of a sample.…”
Section: Introductionmentioning
confidence: 99%